2015
DOI: 10.1016/j.ijgo.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomized controlled trial of mifepristone or placebo before buccal misoprostol for abortion at 14–21 weeks of pregnancy

Abstract: Adding mifepristone before misoprostol can improve the quality of second-trimester abortion care by making the process faster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
(40 reference statements)
0
29
2
1
Order By: Relevance
“…Modak et al [8] in a comparative study of sublingual and vaginal misoprostol in second trimester abortions reported a complete abortion at 24 h of 79.41 % (in sublingual group) and mean IAI of 12.28 h. Ngoc et al [9] in their double blind study reported the mean IAI was statistically shorter for mifepristone plus misoprostol group compared to misoprostol only group (8.1 h and 10.6 h, respectively, with a p value of \0.01). Rasha et al [10] in their study reported mean IAI of 10.4 ± 6.8 h in mifepristone group and 20.6 ± 9.7 h in misoprostol only group. Reduction in induction to abortion interval is likely to improve the acceptability of women [9].…”
Section: Discussionmentioning
confidence: 85%
“…Modak et al [8] in a comparative study of sublingual and vaginal misoprostol in second trimester abortions reported a complete abortion at 24 h of 79.41 % (in sublingual group) and mean IAI of 12.28 h. Ngoc et al [9] in their double blind study reported the mean IAI was statistically shorter for mifepristone plus misoprostol group compared to misoprostol only group (8.1 h and 10.6 h, respectively, with a p value of \0.01). Rasha et al [10] in their study reported mean IAI of 10.4 ± 6.8 h in mifepristone group and 20.6 ± 9.7 h in misoprostol only group. Reduction in induction to abortion interval is likely to improve the acceptability of women [9].…”
Section: Discussionmentioning
confidence: 85%
“…Given recently published evidence, we have added alternative routes for taking misoprostol; in most cases, this has meant the addition of the buccal route, in which the tablets are placed in the cheek for 30 minutes after which any remnants are swallowed. This route has a similar pharmacokinetic profile to the vaginal route.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…In 2012, the International Federation of Obstetrics and Gynecology (FIGO) produced a chart detailing recommended dosages of misoprostol when used alone, for a variety of gynecologic and obstetric indications. In light of new evidence and through expert deliberation, this chart has now been revised and expanded (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Rasha et al, (2015) 8 the mean induction abortion interval in Group A was reported to be 10.46.8h while in Group B it was 20.6 9.7h. Thus, the reduction in the induction abortion interval also improves acceptability of the procedure in women ( Table 5).…”
Section: Induction-abortion-intervalmentioning
confidence: 90%